Recent Developments in European Bank Competition - Sun, Yu (IMF Working Papers; Working Paper ;, 2011)
This paper investigates the degree of bank competition in the euro area, the U.S. and U.K. before and after the recent financial crisis, and revisits the issue whether the introduction of EMU and the euro have had any impact on bank competition. The results suggest that the level of bank competition converged across euro area countries in the wake of the EMU. The recent global financial crisis led to a fall in competition in several countries and especially where large credit and housing booms had preceded the crisis.